Planning for community: understanding diversity in resident experiences and expectations of social connections in a new urban fringe housing estate, Australia. Issue 4 (8th August 2017) - Nicholls, Larissa; Maller, Cecily; Phelan, Kath
ABSTRACT: Master-planned estates are a major source of new housing for growing cities. Much research finds these residential developments lack genuine social connections between residents despite marketing of 'close-knit' community. Selandra Rise is a new residential development on the urban fringe of Melbourne, Australia. The estate was planned with a focus on community infrastructure and resident well-being. The resident population was younger and more culturally diverse than most other master-planned community case studies. A longitudinal research design was used to explore resident understanding, experiences and needs relating to place-based community. Interviews were conducted with residents before moving to the estate and 9–18 months after moving. Some residents considered community as an amenity provided by the master-planned environment that did not require their social participation. Others aspired to make social connections with neighbours but had varying levels of success. Past experiences which contributed to aspirations for connecting with local community, and the ways that these aims were realised or hindered, are discussed. Understanding diverse resident expectations of community and insights from their lived experience are used to make recommendations for planning new neighbourhoods and designing community development programmes.